DEWEY ON CIVIL RIGHTS, TESTING, INTEREST, AND DISCIPLINE: DEMOCRACY AND EDUCATION IN PERSPECTIVE. (7th November 2017) - Rury, John L.; Rice, Suzanne
Abstract : In this essay we consider how the principles evident in Dewey's Democracy and Education would have been evident in response to the civil rights movement that took shape shortly after his death, and to the major educational reform movements of today. While acknowledging that Dewey's views on race and human development were inevitably influenced by his social and intellectual context, we maintain that he was fundamentally opposed to racist ideology and related popular beliefs, and that his deep commitment to democracy as a social process would have made him a staunch supporter of the civil rights movement and associated demands for racial equality. We likewise argue that Dewey would have had deep misgivings about the standards-driven assessment regimes that underlie current national reform efforts. In the end we suggest that Democracy and Education still has much to offer students of education today, and can serve as a helpful guide to those who would seek to change educational practice for the better.